The impact of mine closures/downscaling on small-town economies: An analysis of the Koffiefontein mine - Kale, Oupa Abraham (University of the Free State, 2022)
Over the past 20 years, the South African mining industry has been characterised by mine closure and downscaling. Not only in South Africa, but also in many other countries, local communities, mineworkers, as well as local economies are severely affected by such closures and downscaling. This study looks specifically at the context of the Koffiefontein mine in the Free State province of South Africa and focuses on the effects of unemployment following mine closure. In order to discuss the implication of mine closure in this specific context, the researcher conducted semi-structured interviews with former Koffiefontein mineworkers, municipal officials from the area, as well as the broader community. Snowball sampling was employed to recruit interviewees, who were asked to comment on their lived experience post mine closure, specifically as it relates to their employment. The study shows that mining activities account for this area's main economic activities. Further, the research indicates that in addition to jeopardising the local community and former mineworkers' livelihoods, the closure of the mine contributes to family disintegration, an increase in crime, psychological distress, income loss, and high levels of migration. Based on these and other related social issues discussed in this study, the researcher recommends that programmes be implemented to increase skills transfer and capacity building. This will allow for labour mobility post mine closure.
Dissertation (MDS (Development Studies))--University of the Free State, 2022